Plant Products Affect Growth and Digestive Efficiency of Cultured Florida Pompano (Trachinotus carolinus) Fed Compounded Diets - Lech, Gregory P.; Reigh, Robert C. (PLOS ONE, 2012)
Costs of compounded diets containing fish meal as a primary protein source can be expected to rise as fish meal prices increase in response to static supply and growing demand. Alternatives to fish meal are needed to reduce production costs in many aquaculture enterprises. Some plant proteins are potential replacements for fish meal because of their amino acid composition, lower cost and wide availability. In this study, we measured utilization of soybean meal (SBM) and soy protein concentrate (SPC) by Florida pompano fed compounded diets, to determine the efficacy of these products as fish meal replacements. We also calculated apparent digestibility coefficients (ADCs) for canola meal (CM), corn gluten meal (CGM), and distillers dried grains with solubles (DDGS), following typical methods for digestibility trials. Juvenile Florida pompano were fed fish-meal-free diets containing graded levels of SBM and SPC, and weight gain was compared to a control diet that contained SBM, SPC, and fish meal. Fish fed diets that contained 25–30 percent SBM in combination with 43–39 percent SPC had weight gain equivalent to fish fed the control diet with fish meal, while weight gain of fish fed other soy combinations was significantly less than that of the control group. Apparent crude protein digestibility of CGM was significantly higher than that of DDGS but not significantly different from CM. Apparent energy digestibility of DDGS was significantly lower than CGM but significantly higher than CM. Findings suggested that composition of the reference diet used in a digestibility trial affects the values of calculated ADCs, in addition to the chemical and physical attributes of the test ingredient.